2007
DOI: 10.1055/s-2006-955978
|View full text |Cite
|
Sign up to set email alerts
|

Plastidic trnFUUC Pseudogenes in North American Genus Boechera (Brassicaceae): Mechanistic Aspects of Evolution

Abstract: The origin and maintenance of a plastidic tandem repeat next to the TRNF (UUC) gene were analyzed in the genus BOECHERA in a phylogenetic context and were compared to published analogous examples that emerged in parallel in the Asteraceae and Juncaceae, respectively. Although we identified some features common to these taxonomic groups with respect to structure and origin of the region, obvious differences were encountered, which argue against a specific mechanism or evolutionary principle underlying the paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 101 publications
(158 reference statements)
0
12
1
Order By: Relevance
“…This leads to the assumption of complex or at least different molecular read mechanism driven development and evolution. It has been previously concluded that tandemly repeated trnF (GAA) pseudogenes are undergoing parallel independent changes which are mediated by complex processes of illegitimate recombination (see Dobeš et al 2007). Ansell et al (2007) studying trnF (GAA) pseudogenes in Arabidopsis lyrata (L.) O'Kane and Al-Shehbaz populations found that disperse repeats which share similar secondary structure patterns interact and facilitate reciprocal exchange of structural motifs between copies through intra-and intermolecular recombinations.…”
Section: Resultsmentioning
confidence: 99%
“…This leads to the assumption of complex or at least different molecular read mechanism driven development and evolution. It has been previously concluded that tandemly repeated trnF (GAA) pseudogenes are undergoing parallel independent changes which are mediated by complex processes of illegitimate recombination (see Dobeš et al 2007). Ansell et al (2007) studying trnF (GAA) pseudogenes in Arabidopsis lyrata (L.) O'Kane and Al-Shehbaz populations found that disperse repeats which share similar secondary structure patterns interact and facilitate reciprocal exchange of structural motifs between copies through intra-and intermolecular recombinations.…”
Section: Resultsmentioning
confidence: 99%
“…Recombination by this method could act to increase pseudogene variation through uneven crossing over [8,9] (Appendix 1).…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of universal primers [10] the non-coding trnL (UAA)-trnF(GAA) intergenic spacer region (trnL-F IGS) of the chloroplast genome has been extensively utilized for plant evolutionary analysis [9,[11][12][13][14] (Appendix 2). In the Brassicaceae, the trnL-F region from at least 20 genera has been documented to contain multiple copies of a duplicated trnF pseudogene [11,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this will be mediated by short repeats formed by slip-strand mispairing (Ogihara et al, 1988), and intermolecular recombination between two genome copies of the plastids because the plastid contains a large number of copies of the chloroplast genome. Recombination by this method could act to increase pseudogene variation through uneven crossing over (Dobes, 2007). The difference in copy number of pseudogenes can be used in genetic diversify studies as well as classification.…”
Section: Chloroplast Transfer Rnas (Trnas)mentioning
confidence: 99%